REQUIREMENTS TO STUDENT AND TEACHER INFORMATION SYSTEM - Kruglyk, V.S. (Journal of Information Technologies in Education (ITE), 2013)
An issue of creating and introduction of work organization support software for students and teachers at universities is topical. The article describes requirements of student and teacher information system for Ukrainian universities. The aim of the article is to examine, analyze and offer general approaches to building services of work organization support system for teachers and students at universities